Empowering Housewives through Local Food-Based Natural Sweetener Production Training - Anik Pujiati; Dittha Puti Sarasvati Ramli; Kristiyanto Kristiyanto; Retariandalas Retariandalas; Saring Ariyanto (ADI Pengabdian Kepada Masyarakat, 2026)
The increasing prevalence of diabetes mellitus highlights the need for public education on healthier sugar consumption and the utilization of local food resources as natural sweetener alternatives. Cassava and sweet potatoes are starch-rich commodities with the potential to be processed into natural sweeteners through enzymatic hydrolysis. This community service program aimed to improve the knowledge and practical skills of housewives in producing natural sweeteners from cassava and sweet potatoes while introducing simple enzymatic food-processing technology. The program was conducted in Grand Depok City Housing, Melati Sector, in December 2025 and involved local housewives as participants. Activities included health education, demonstrations, hands-on practice, and mentoring. Program evaluation was carried out using pretests, posttests, practical observations, and 20 participant satisfaction questionnaires. The evaluation indicated a mean satisfaction score of 4.75 (excellent category), while the average knowledge score increased from 7.67 in the pretest to 11.67 in the posttest, representing a 52.15% improvement. Participants also demonstrated better understanding of enzymatic hydrolysis, healthier sugar consumption, and the potential of cassava and sweet potatoes as value-added local food products. The program effectively enhanced participants health literacy and food-processing skills, demonstrating its potential as a community empowerment model that supports food diversification and value-added utilization of local agricultural resources.